2018
DOI: 10.1371/journal.ppat.1006830
|View full text |Cite
|
Sign up to set email alerts
|

Fab-based inhibitors reveal ubiquitin independent functions for HIV Vif neutralization of APOBEC3 restriction factors

Abstract: The lentiviral protein Viral Infectivity Factor (Vif) counteracts the antiviral effects of host APOBEC3 (A3) proteins and contributes to persistent HIV infection. Vif targets A3 restriction factors for ubiquitination and proteasomal degradation by recruiting them to a multi-protein ubiquitin E3 ligase complex. Here, we describe a degradation-independent mechanism of Vif-mediated antagonism that was revealed through detailed structure-function studies of antibody antigen-binding fragments (Fabs) to the Vif comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
25
0
1

Year Published

2018
2018
2019
2019

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 48 publications
1
25
0
1
Order By: Relevance
“…While it is possible that all APOBEC3 proteins could rigidify the VCBC complex to the same extent and in the same conformation, other intrinsically disordered proteins have been demonstrated to adopt different conformations with their multiple binding partners (58,59). Recent work by Binning et al also showed that Vif disrupts the APOBEC3 packaging into virions by a degradation-independent mechanism that occurs when CUL5 is prevented from binding to the VCBC complex (19 which all simulations were initiated. c) VCBC structure (Vif is shown in pink, CBF- in green, of VCBC complex bound to dT14 in 50 mM NaCl (red) corresponds to an experimental molecular mass of 135 kDa, which is consistent with the theoretical molecular weight for a monomer of 66 kDa, indicating that the complex is a dimer.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While it is possible that all APOBEC3 proteins could rigidify the VCBC complex to the same extent and in the same conformation, other intrinsically disordered proteins have been demonstrated to adopt different conformations with their multiple binding partners (58,59). Recent work by Binning et al also showed that Vif disrupts the APOBEC3 packaging into virions by a degradation-independent mechanism that occurs when CUL5 is prevented from binding to the VCBC complex (19 which all simulations were initiated. c) VCBC structure (Vif is shown in pink, CBF- in green, of VCBC complex bound to dT14 in 50 mM NaCl (red) corresponds to an experimental molecular mass of 135 kDa, which is consistent with the theoretical molecular weight for a monomer of 66 kDa, indicating that the complex is a dimer.…”
Section: Discussionmentioning
confidence: 99%
“…The VCBC complex, consisting of consensus Vif (19), CBF- (residues 1-165), EloB (residues 1-118), and EloC (residues 17-112), was co-expressed in E. coli BL21 DE3 Star cells as described (19). Briefly, cells were grown to mid-log phase at 37 C followed by induction with To express the VCBC complex with 13 C isotope labels on the methyl groups (ILVMA) for NMR spectroscopy, the BL21 DE3 Star cells were grown in M9 minimal media with trace metals (36).…”
Section: Protein Expression and Purificationmentioning
confidence: 99%
See 3 more Smart Citations